Pharmacokinetics of cytosine arabinoside in patients with acute myeloid leukaemia. - Harris, A L (1979)
1 The pharmacokinetics of cytosine arabinoside were studied after a single i.v. bolus of 2 mg/kg ara-C in patients with newly diagnosed untreated AML, using a bioassay and GC-MS method to measure the plasma concentrations. 2 Most patients showed a bi- or tri-phasic decline in plasma concentrations with time. Plasma clearance was 3.9 to 18.1 l/min as measured by the GC-MS method, and terminal half-lives varied from 7--107 min. 3 There was poor correlation of the GC-MS assay with the bioassay, probably because the latter was interfered with by the release of endogenous nucleosides from blasts after after ara-C. 4 Plasma concentrations were measured by GC-MS during continuous infusions in 14 patients. Plasma clearances were much lower than after a bolus, 0.39 to 5.25 l/min. 5 There was no correlation of response (remission or fall in peripheral blast count) with exposure to ara-C calculated from infusion dose, clearance and duration of infusion. 6 This study shows that ara-C pharmacokinetics varies markedly from patient to patient and that there is a wide range in the plasma concentrations associated with therapeutic response.